Diet composition of the lizard Lacerta viridis (Laurenti, 1768) (Reptilia: Lacertidae) in Bulgaria confirm its generalistic feeding behaviour - Emiliya Vacheva; Borislav Naumov (Historia naturalis bulgarica, 2024)
The eastern green lizard (Lacerta viridis) is a mostly insectivorous species, based on multiple studies from across its range. However, for Bulgaria the published data of such kind are limited to five publications. We investigated faecal samples from a total of 60 individuals of free-ranging L. viridis obtained from two localities in western Bulgaria. Our aim was to clarify the diet regarding its taxonomic composition, as well as some physical characteristics of the prey like hardness and evasiveness. For one of the study sites we compared the realised trophic niche (prey items from the faecal pellets) with the fundamental niche (invertebrates collected via pit-fall traps exposure). In our results, two invertebrate taxa had the largest share (both in frequency and abundance) in the food spectrum of L. viridis: Araneae and Coleoptera), respectively 21.2% and 17.6%. Regarding specific prey selectivity, analysis showed that Lepidoptera are most preferred (E* = 0.68), and Formicidae - most avoided prey items (E* = -0.79). We registered several cases of saurophagy (in four samples) and keratophagy (in two samples), two types of dietary items, which have not been reported for L. viridis so far.